TANTANGAN HUKUM DALAM PELAKSANAAN AKAD IJARAH DI PERBANKAN SYARIAH - Edy, Sarwo (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2022)
Abstract The implementation of Ijarah contracts in Islamic banking faces several legal challenges that affect its effectiveness and acceptance. This study aims to explore these challenges by analyzing the legal framework, regulatory requirements, and practical issues encountered by Islamic financial institutions. The main legal challenges include inconsistencies in regulatory interpretations, lack of standardized contracts, and the complexity of integrating Sharia principles with national laws. This research highlights the need for harmonized regulations and clearer guidelines to enhance the operational efficiency and legal robustness of Ijarah contracts. Recommendations for policymakers and banking practitioners are provided to address these challenges and promote the growth of Islamic finance. This study indicates that the legal challenges in implementing Ijarah contracts in Islamic banking are complex issues that require serious attention. With the right strategies and cooperation among various stakeholders, these challenges can be overcome to ensure Sharia compliance and the sustainability of Islamic banking operations. Keywords: Ijarah contracts, Islamic banking, legal challenges, regulatory framework, Sharia compliance